Association of solvents improves selected properties of experimental dental adhesives - Francisbênia Alves Silvestre; Vitaliano Gomes de Araújo Neto; Marcelo Giannini; Tainah Oliveira Rifane; Karen Evellin Moura Cordeiro; Samara Tabata Cavalcante Braga Medeiros; Diego Lomonaco; Madiana Magalhães Moreira; Adyson Herbert Correia Alves; Victor Pinheiro Feitosa (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract: The aim of the study was to evaluate how the association of solvents (tetrahydrofuran [THF], dimethyl sulfoxide [DMSO], ethanol [ET] or acetone [ACT]) with experimental dental adhesives affects selected properties of experimental dental adhesives and dentin bond durability. Six adhesive combinations were prepared containing: 30 % ET, 30 % ACT, 30 % THF, 28 % ET + 2 % DMSO (ET+DMSO), 15 % ethanol + 15 % THF (ET+THF), or 28 % THF + 2 % DMSO (THF+DMSO). Thirty-six molars (n = 6) were cut to expose the coronary dentin, and were randomly divided according to the adhesives. They were restored, and then cut into resindentin sticks (1 mm²), and stored in distilled water for 24 h or 6 months, until conducting the microtensile bond strength and nanoleakage tests. Other experiments performed with adhesives included viscosity assessment using a rheometer, and degree of conversion using Fourier-transform infrared spectroscopy (FTIR). The data were analyzed statistically using two-way ANOVA and Tukey's test (p < 0.05). The adhesive formulated exclusively with THF showed the highest viscosity, followed by ET+THF, which obtained the highest degree of conversion compared to ET, and THF alone. ET+DMSO obtained the highest 24-h and aged bond strengths (p < 0.05). ET+THF increased the nanoleakage slightly after 6 months, but attained the only gap-free adhesive interface among all the groups. The combination of alternative solvents, particularly THF, with conventional ones (ET) has improved chemical properties, and the dentin bonding of experimental simplified adhesives.